Strategi Guru Kelas dalam Meningkatkan Kemampuan Membaca Anak melalui Media Flash Card: Classroom Teacher Strategies in Improving Children's Reading Ability via Media Flash Card - Witasari, Rinesti; Rahma, Tiara Aulia (Institut Agama Islam Sunan Giri Ponorogo, 2022)
Reading is one of the language skills that every individual must have. The success of a child in participating in learning at school is influenced by the mastery of reading skills. Therefore, a strategy is needed to improve reading skills in children from an early age. The purpose of this article is to find out how the strategies used by teachers improve children's reading skills. This research is a type of descriptive qualitative research with data collection conducted by means of observation, interviews, and documentation. The research was carried out in July in the odd semester of 2022. Observations were made to look at the environmental situation of Dharma Wanita Kindergarten, whether the location was the object of research, then interviews were conducted by asking several questions to Dharma Wanita Kindergarten teachers about teaching strategies in teaching, then documentation in the form of photographs when the researcher was interviewing the principal at Dharma Wanita Kindergarten. The results of research on the learning process in Dharma Wanita Kindergarten by using Flash card media or playing cards, namely, children begin to be able to recognize the letters of the alphabet and can memorize. In addition, during the learning process, the teacher used good strategies, including strategies with letter cards, strategies with interesting pictures, strategies with real objects, and strategies with singing.